2018
DOI: 10.1002/pd.5272
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with multigene carrier panels in the reproductive setting

Abstract: ObjectivesExpanded carrier testing is acknowledged as an acceptable strategy for carrier testing by the American College of Obstetrics and Gynecology. Limited studies have investigated positivity rates of expanded carrier panels. We describe our experience with 3 commercial laboratory panels varying in size from 3 to 218 disorders.MethodsWe reviewed outcomes for 3 multigene carrier screening panels: trio (3 diseases), standard (23 diseases), and global (218 diseases). All panels used targeted genotype analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
1
3
1
Order By: Relevance
“…Our findings are consistent with the expectation and previous reports that increasing the number of genes in a panel results in an increase in the number of individuals identified as carriers for a single genetic condition and for individuals identified as carriers for multiple genetic conditions (Arjunan et al, ; Baskovich et al, ; Haque et al, ; Lazarin et al, ; Terhaar et al, ). Our pan‐ethnic expanded carrier screening panel of 87 genes increased the carrier detection rate among AJ individuals by approximately 50% compared with the 18‐gene AJ panel and by approximately 100% compared with the nine ACMG genes recommended for AJ carrier screening.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with the expectation and previous reports that increasing the number of genes in a panel results in an increase in the number of individuals identified as carriers for a single genetic condition and for individuals identified as carriers for multiple genetic conditions (Arjunan et al, ; Baskovich et al, ; Haque et al, ; Lazarin et al, ; Terhaar et al, ). Our pan‐ethnic expanded carrier screening panel of 87 genes increased the carrier detection rate among AJ individuals by approximately 50% compared with the 18‐gene AJ panel and by approximately 100% compared with the nine ACMG genes recommended for AJ carrier screening.…”
Section: Discussionsupporting
confidence: 93%
“…Baskovich et al () analyzed exome data for 128 AJ individuals and identified 163 mutations causing 103 conditions, but the intent was to identify new pathogenic mutations to include in an AJ panel, not to specify which positive results would have been obtained with a recommended AJ panel. Terhaar et al () detailed a commercial laboratory's experience using three different carrier screening panels, comparing positive rates for patients tested for carrier status for either three, 23, or 218 conditions. The population was pan‐ethnic, with nearly half identified as Caucasian and fewer than 0.5% (322 of approximately 75,000 individuals) as AJ.…”
Section: Introductionmentioning
confidence: 99%
“…For individuals of AJ origin, the CCR found in our study was 58.5% and therefore higher than the 37.5% (1:2.7) 19 and 40% (1:2.5) 20 published in AJ cohorts, or the 36% (1:2.8) 21 reported in a pan‐ethnic population.…”
Section: Discussioncontrasting
confidence: 75%
“…Applications for WES and targeted DNA (panel) sequencing (n=169, 24%) include identification of pathogenic mutations (mostly point mutations, small insertions and deletions) that can aid in diagnosis of monogenic autoinflammatory diseases and vasculitis, 48 FMF, 49 gout 50 or familial RA, SLE and primary Sjögren’s syndrome 51 or Uveitis. 52 Of note, while HTS assays are powerful tools for large cohorts, we find many case reports using WES and gene panel sequencing in, for example, in a young patient with cutaneous vasculitis 53 or JIA, 54 as well as in a patient with RA experiencing immune dysregulation syndrome after abatacept therapy.…”
Section: Resultsmentioning
confidence: 99%